Impact of White Blood Cell Count After Percutaneous Coronary Intervention on Long-Term Prognosis in Patients with Unstable Angina Pectoris: A Single-Center Retrospective Observational Cohort Study - Zhang Z; Wang H; Wang R; She Z; Liang X; Liu H; Kou X; Wang S (Vascular Health and Risk Management)
Zhiyuan Zhang,1– 3,* Heyan Wang,4,* Ruiyu Wang,5 Zeyu She,6 Xingyue Liang,6 Huiyi Liu,7 Xuemeng Kou,1 Shipeng Wang1– 3 1Department of Cardiology, the Second Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 2Key Laboratory of Myocardial Ischemia, Ministry of Education, Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 3State Key Laboratory of Frigid Zone Cardiovascular Diseases (SKLFZCD), Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 4Department of Cardiology, Central Hospital of Dalian University of Technology, Dalian, Liaoning Province, People’s Republic of China; 5Department of Cardiology, the First Affiliated Hospital of Medical School, Xi’an Jiaotong University, Xi’an, Shaanxi Province, People’s Republic of China; 6School of Basic Medicine, Harbin Medical university, Harbin, Heilongjiang Province, People’s Republic of China; 7Department of Cardiology, the First Affiliated Hospital of Peking University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shipeng Wang, Department of Cardiology, 2nd Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang Province, 150086, People’s Republic of China, Tel +86 13654504286, Fax +86 86296225, Email guoyunqaz@126.comObjective: An association between white blood cell count (WBC-C) before percutaneous coronary intervention (PCI) and prognosis has been established in patients undergoing PCI. However, the effect of WBC-C after PCI on the long-term prognosis of patients with unstable angina pectoris (UA) is unclear.Methods: A retrospective cohort study was conducted in 1811 consecutive patients with UA. The changes of WBC and subgroup counts before and in the early postoperative stages after PCI were observed by paired Wilcoxon signed-rank test. The Kaplan–Meier method and COX proportional regression model were used to evaluate the association between the incidence of 5-year endpoint events and post-PCI leukocytosis.Results: Leukocytosis and neutrocytosis within 24 hours after PCI were observed in majority of patients with UA, while lymphocyte count significantly decreased after PCI in those patients. There were no significant differences in 5-year all-cause mortality and major adverse cardiovascular and cerebrovascular events (MACCE) between patients in the post-PCI leukocytosis and the control group. However, the 5-year incidence of major adverse cardiovascular events (MACE) was significantly increased in the post-PCI leukocytosis group (p = 0.017, Log rank test). Leukocytosis after PCI was independently associated with the occurrence of MACE (hazard ratio: 1.36; 95% confidence interval: 1.06– 1.75; p = 0.015).Conclusion: Peripheral WBC and neutrophil counts within 24 hours after PCI significantly increased in response to PCI in patients with UA, while lymphocyte count significantly decreased after PCI in those patients. The post-PCI leukocytosis offered predictive value for an increased risk of MACE for up to 5 years in patients with UA.Keywords: white blood cell count, percutaneous coronary intervention, unstable angina pectoris, leukocytosis, major adverse cardiovascular events